Penerapan Metode Diskusi Dan Tanya Jawab Dalam Meningkatkan Motivasi Belajar Ipa Siswa Kelas V Min Kauman Utara Jombang - Musa’adatul Fithriyah (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2017)
A defined method or procedure used to achieve certain goals. With regards to learning methods are defined as a way of presenting learning materials for learners to achieve its intended purpose. Developing teaching methods is one of the efforts to improve the quality of student learning. An educator is required to master the method because it can help to facilitate its work in delivering course material and the most important methods used so that students can actively participate in the learning process. Reality on the ground science subjects is low quality because it has not reached the desired target adequately. This is caused in part by the methods used by teachers in learning. The method used is felt still less create a conducive atmosphere and fun for students. This led to the mentality of the students consider that science as difficult subjects so Siwa less passionate in learning. The purpose of this research is to know the implementation of discussion and question and answer method can increase students' motivation Subjects IPA / science Class V in MIN utara Kauman Jombang.  This research is a classroom action research (PTK) with a research model used is the model Kurt Lewin. Kurt Lewin explained that there are four things that must be done in the process of action research that is planning, action, observation and reflection. The results showed the application of the method of discussion and question and answer method can gradually increase students' motivation that impact on student achievement. Proven academic achievement when it happened in the first cycle students the acquisition value of a minimum of 75 and maximum of 88, while in the second cycle showed a significant increase post-test results indicate the acquisition value of a minimum of 76 and maximum of 96. Based on the results of study, we can conclude the success of student learning depends not only on the intelligence of children alone, but it also depends on how educators use appropriate methods in learning as evidenced by the results of applying the method of discussion and question and answer can increase students' motivation in class V-C MIN Kauman utara JombangKeywords: Learning Method, Motivation, IPA/Science